Performance analyses of a multi-carrier code division CDMA wireless communication system with fading (Rayleigh and Rician) - Mahmood, Saad; Hossain, M.M. Wasid; Abdullah, Abu Sakib (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2010.